Hi dear Katie, well dear its easy.
x^2+ 3x = 0
{ factor 'x' }
x( x + 3) = 0
x = 0
OR
x+3 = 0 ; x = -3
& thats all.
Good Luck sweetheart.
2006-09-10 08:53:50
·
answer #1
·
answered by sweetie 5
·
0⤊
0⤋
Both the x^2 and the 3x contain at least one x. So, factor out an x, and you'll get x(x+3). Notice that if you distribute that x back out again, you'll end up with the original problem, so you know you're right so far.
Now, the only way to multiply two numbers together and get zero is if one of them already is zero. Therefore, if x(x+3)=0, either x=0 or x+3 =0.
Solve both equations to get your two answers: x={0,-3}
2006-09-10 15:23:10
·
answer #2
·
answered by Mehoo 3
·
0⤊
0⤋
x^2 + 3x = 0
To factor, you need to know what x^2 and 3x have in common. Well, you know that x times x is x squared and that 3x means 3 times x. That means that they have x in common. So, divide out the x.
x(x + 3) = 0
You know that anything times 0 is 0, so either x or x + 3 has to equal zero in order for the given equation to be true.
x = 0
x + 3 = 0
x = -3
So your answer is
x = -3 or 0
2006-09-10 15:28:35
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x^2 +3x= 0
you see that the terms on the left hand side contains a common factor x
by extracting this factor
the left hand side will be: x(x + 3)
which is a product of two factors while the right hand side is zero
that is: x(x + 3)= 0
which gives one of two conclusions
Either x = 0 or x + 3 = 0
that is:
Either x = 0 or x = -3
2006-09-10 15:21:57
·
answer #4
·
answered by Hassan g 2
·
0⤊
0⤋
X^2+3X = 0
First remove the X;
X(X+3) - - - notice then when I times X by X i get Xsquared and when I times x by 3 I get 3x
set each x equal to zero
therefore: x = 0, x=-3.
2006-09-10 15:19:58
·
answer #5
·
answered by bakergrl5 2
·
0⤊
0⤋
x^2 + 3x = 0
x(x+3) = 0
2006-09-10 17:21:15
·
answer #6
·
answered by spoof ♫♪ 7
·
0⤊
0⤋
x^2 + 3x = 0
x(x + 3) = 0
x = 0 or -3
2006-09-10 19:56:30
·
answer #7
·
answered by Sherman81 6
·
0⤊
0⤋